Targeting CX3CR1 inhibits silica-induced epithelial-mesenchymal transition and pulmonary fibrosis in mice via the NF-κB signaling pathway - Jiaxin Zhang; Yuhua Wang; Chuanyi Huo; Xukun Jiao; Xinying Zeng; Jingya Li; Zhonghui Zhu; Yifei Wang; Lin Tian; Yan Wang (Toxicology, 2026)

Identification of Closantel as a small-molecule inhibitor of the compact CRISPR-Cas RNA editor Cas13bt3 - Xulong Chen; Binbin Zhan; Ruyi Shi; Jingxuan Chen; Zhonghui Lin; Zuoan Li (Molecular Diversity, 2026)

Research on external defect inspection of subsea pipelines and cables using subsea dry habitat and 3D imaging technology - Hai Zhu; Jiawang Chen; Zhangyong Jin; Kaichuang Wang; Peiwen Lin; Yuan Lin; Yuping Fang; Peng Zhou; Zhonghui Zhou; Yuhong Wang; Xu Gao; Yuanjie Chen (Ocean & Coastal Management, 2026)

Cx3cr1 depletion ameliorates lipid metabolic dysregulation and pulmonary fibrosis induced by silica - Enna Hu; Yiru Wang; Zhechen Li; Jiaxin Zhang; Weifan Huang; Jiawen Shen; Dailin Liu; Zhonghui Zhu; Lin Tian; Yan Wang (Chemico-Biological Interactions, 2026)

In-situ remediation of Cr(VI) contaminated groundwater by synergistic oxalic acid-ethanol reduction: Mechanistic insights and sand tank validation - Wenwen Lin; Yang Liu; Zhonghui Han; Chengye Wang; Xiaoxu Zhang; Taigang Ma; Hejun Ren (Journal of Cleaner Production, 2025)

A robust method for quantitative detection of β-1,3-glucan using Limulus polyphemus factor Gα fragment - Andong Zhou; Yitong Li; Yuanning Wang; Yibing Wang; Zhonghui Qiao; Kevin H. Mayo; Zihan Zhao; Lin Sun (Carbohydrate Polymers, 2025)

Ferroptosis and iron metabolism drive fibroblast activation in silicosis: insights from a novel 3D lung matrix model - Chenzhao Song; Xinying Zeng; Jiaxin Wang; Wenming Xue; Yan Wang; Yifei Wang; Lin Tian; Zhonghui Zhu (Journal of Molecular Medicine, 2025)

Pulmonary microbiota affects silica-induced pulmonary fibrosis through activation of the PI3K/AKT-mediated senescence in alveolar epithelial cells - Chuanyi Huo; Qiyue Jia; Xukun Jiao; Qiyue Jiang; Xinying Zeng; Jiaxin Zhang; Yan Wang; Zhonghui Zhu; Lin Tian (Journal of Hazardous Materials, 2025)

Immuno- and gut microbiota-modulatory activities of β-1,6-glucans from Lentinus edodes - Xian Qu; Yahui Ji; Jieyi Long; Donglin Zheng; Zhonghui Qiao; Yue Lin; Chang Lu; Yifa Zhou; Hairong Cheng (Food Chemistry, 2025)

Air-sea CO2 exchange in the western Pacific influenced by monsoon and giant diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Journal of Asian Earth Sciences, 2024)

Discovery of KPT-6566 as STAG1/2 Inhibitor sensitizing PARP and NHEJ Inhibitors to suppress tumor cells growth in vitro - Qinwei Zhu; Xuening Chen; Zhonghui Lin (DNA Repair, 2024)

Silica aggravates pulmonary fibrosis through disrupting lung microbiota and amino acid metabolites - Chuanyi Huo; Xukun Jiao; Yan Wang; Qiyue Jiang; Fuao Ning; Jiaxin Wang; Qiyue Jia; Zhonghui Zhu; Lin Tian (Science of The Total Environment, 2024)

East Asian Winter Monsoon and enhanced stratification in the western Pacific promoted giant marine diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Quaternary Science Reviews, 2024)

High-temperature energy storage with a new tri-layers polymer composites via hybrid assembly engineering - Fei Wen; Hongbin Yuan; Mengquan Jiang; Pingan Yang; Jian Wang; Lin Zhang; Lili Li; Gaofeng Wang; Wenjun Li; Wei Wu; Zhonghui Shen; Shujun Zhang (Chemical Engineering Journal, 2024)

Self-supporting high-entropy Co-Cr-Fe-Ni-Nb oxide electrocatalyst with nanoporous structure for oxygen evolution reaction - Yuhan Lin; Wence Xu; Zhonghui Gao; Yanqin Liang; Hui Jiang; Zhaoyang Li; Shuilin Wu; Zhenduo Cui; Huaijun Sun; Huifang Zhang; Shengli Zhu (Chemical Engineering Journal, 2024)

Fractional nutrient uptake model of plant roots - Yue Wang; Mingfang Lin; Quanbiao Gong; Zhonghui Ou (BioSystems, 2024)

Dt1 inhibits SWEET-mediated sucrose transport to regulate photoperiod-dependent seed weight in soybean - Xiaoming Li; Zhonghui Chen; Haiyang Li; Lin Yue; Cuirong Tan; Hongjie Liu; Yilong Hu; Yuhua Yang; Xiani Yao; Lingping Kong; Xiang Huang; Bin Yu; et al. (Molecular Plant, 2024)

Investigation of the mechanism of silica-induced pulmonary fibrosis: The role of lung microbiota dysbiosis and the LPS/TLR4 signaling pathway - Qiyue Jia; Hongwei Wang; Yan Wang; Wenming Xue; Qiyue Jiang; Jiaxin Wang; Fuao Ning; Zhonghui Zhu; Lin Tian (Science of The Total Environment, 2024)

A coupled model applied to complex river–lake systems - Qi Zhang; Chesheng Zhan; Yueling Wang; Haoyue Zhang; Zhonghui Lin (Hydrological Sciences Journal, 2024)

Analytical solution of Nye–Tinker–Barber model by Laplace transform - Yue Wang; Wenting Lin; Zhonghui Ou (BioSystems, 2023)

To cheat or to treat? Fungus gnat pollination in Aspidistra - Wei Lin; Yuanqing Xu; Yuhui Jiang; Zhonghui Ma (Ecology, 2022)

A comparative study on the model of PM2.5 direct or indirect interaction with bronchial epithelial cells - Yan Wang; Xin Zuo; Fuyang Jiang; Lin Hou; Qiyue Jiang; Zhonghui Zhu; Lin Tian (Environmental Science and Pollution Research, 2022)

Dynamics and responses of vegetation to climatic variations in Ziya-Daqing basins, China - Farong Huang; Xingguo Mo; Zhonghui Lin; Shi Hu (Chinese Geographical Science, 2016)

Exploring spatiotemporal patterns and physical controls of soil moisture at various spatial scales - Jianxiu Qiu; Xingguo Mo; Suxia Liu; Zhonghui Lin (Theoretical and Applied Climatology, 2014)

Preliminary analysis of spatiotemporal pattern of global land surface water - Xin Cao; Jun Chen; LiJun Chen; AnPing Liao; FangDi Sun; Yang Li; Lei Li; ZhongHui Lin; ZhiGuo Pang; Jin Chen; ChaoYing He; Shu Peng (Science China Earth Sciences, 2014)

Exploring the interannual and spatial variations of ET and GPP with climate by a physical model and remote sensing data in a large basin of Northeast China - Xingguo Mo; Suxia Liu; Dejuan Meng; Zhonghui Lin (International Journal of Climatology, 2014)
Variations in evapotranspiration ( ET ) and gross primary production ( GPP ) due to climatic fluctuations deserve specific considerations for sustainable water and agricultural management. A Vegetation Interface Processes ( VIP ) model assimilated with Terra‐ MODIS remotely sensed leaf area index was used to simulate their spatial and temporal patterns from 2000 to 2010 in the Songhua River Basin of Northeast China at 1‐km grid and 1‐h time step. The predicted ET and GPP were well verified with the eddy covariance measurements, and the ET was in agreement with that derived from water balance. Over the whole basin, average annual precipitation (P), ET , GPP and water use efficiency are 458 mm, 374 mm, 1067 gC m −2 and 2.86 gC m −2 mm −1 , respectively. Both ET and GPP display significantly spatial variability, with ET presenting different and good relationships with precipitation for different kinds of land use covers ( LUCs ); and GPP a unified good relationship across almost all the LUCs except water body. Over the years from 2000 to 2010, Normalized Difference Vegetation Index ( NDVI ), especially crop NDVI , experienced a trend of increasing. GPP showed no significant trend. ET showed an increasing trend for cropland and grassland, a decreasing trend in water body and wetland, no significant trend for other vegetation types and a weakly increasing trend for the whole basin. Annually, ET roughly follows precipitation, whereas GPP was mainly regulated by radiation (Rn). The inter‐annual variability for the eco‐hydrological elements with the order of the coefficient of variation (CV) being P (0.13) > E C (0.055) > ET (0.05) > Rn (0.037) > GPP (0.019) > NDVI (0.01) is less than their spatial variability with the order of CV being E C (0.23) > P (0.22) > GPP (0.19) > ET (0.15) > Rn (0.05). The highest spatial variability of ET and GPP in grassland implies the incurring problem of degradation in western basin. The low spatial variability in paddy relates agricultural management.

Intercomparison of microwave remote-sensing soil moisture data sets based on distributed eco-hydrological model simulation and in situ measurements over the North China Plain - Jianxiu Qiu; Xingguo Mo; Suxia Liu; Zhonghui Lin; Lihu Yang; Xianfang Song; Guangying Zhang; Vahid Naeimi; Wolfgang Wagner (International Journal of Remote Sensing, 2013)

Impacts of climate change on crop evapotranspiration with ensemble GCM projections in the North China Plain - Xingguo Mo; Ruiping Guo; Suxia Liu; Zhonghui Lin; Shi Hu (Climatic Change, 2013)

Emergy Assessment of a Wheat-Maize Rotation System with Different Water Assignments in the North China Plain - Shi Hu; Xingguo Mo; Zhonghui Lin; Jianxiu Qiu (Environmental Management, 2010)

Endophytic fungi from a pharmaceutical plant, Camptotheca acuminata: isolation, identification and bioactivity - Xiang Lin; Chunhua Lu; Yaojian Huang; Zhonghui Zheng; Wenjin Su; Yemao Shen (World Journal of Microbiology and Biotechnology, 2007)

Estimating the minimum in-stream flow requirements via wetted perimeter method based on curvature and slope techniques - Suxia Liu; Xingguo Mo; Jun Xia; Changming Liu; Zhonghui Lin; Baohui Men; Lina Ji (Journal of Geographical Sciences, 2006)